Oxytocin-Motivated Ally Selection is Moderated by Fetal Testosterone Exposure and Empathic Concern - Kret, Mariska E.; De Dreu, Carsten (Frontiers in Neuroscience, 2013)
In humans, the hypothalamic neuropeptide oxytocin shifts the individual’s focus on self-interest towards group-serving cognitions and decision making. Here we examine this general tendency in the context of group formation, where individuals included into their group (or not) 18 targets morphed as having low or high-threat potential (with high-threat targets being beneficial to group-interests but potentially hurting the recruiter’s self-interest). Ninety healthy males self-administered oxytocin or placebo in a randomized double-blind, placebo-controlled study design, had their hands scanned to derive fetal testosterone vs. estradiol exposure from their 2D:4D ratio, and self-reported on their chronic empathic concern. Multilevel regression models revealed that when given oxytocin rather than placebo, individuals with low fetal testosterone priming included low-threat targets more and high-threat targets (somewhat) less. Individuals with high fetal testosterone (i.e., low estradiol) exposure, however, included high-threat targets more, and low-threat targets less when given oxytocin rather than placebo. Second, when given oxytocin rather than placebo, individuals with low empathic concern included low-threat targets more and high-threat targets less. Individuals with high empathic concern, however, included high-threat targets more, and low-threat targets less when given oxytocin rather than placebo. We conclude that oxytocin shifts the individual’s focus from self to group-serving cognition and decision making, and that these tendencies are stronger for males with high rather than low fetal testosterone exposure, and high rather than low empathic concern. Implications and avenues for future research are discussed.